Corruption, natural capital and economic development: A dynamic GMM analysis - Joshua Ping Ang; Jason Patalinghug (Review of Economic Analysis (REA), 2025)
Using a dynamic panel dataset of 150 countries for the period of 2006-2018 and a twostep system GMM estimation model, this paper shows that natural resources have a positive effect on economic development while holding corruption constant. Our findings support the notion that natural resources have a positive effect on the economy of a nation. When a country has less corruption, it improves the appropriation of economic gains from natural resources which serves as natural capital that would drive further capital accumulation and further development. We also find that physical capital, human capital, and freedom from corruption show strong positive effects on economic development, controlling for other economic and institutional variables.
Keywords: O47; Q32; 330; Corruption; Economic Development; Dynamic Panel Study; NaturalResources; Physical Capital; Human Capital